Оптимизация производства инструментальных частей режущих штампов - Амиров, Алтай; Мамедзаде, Тамерлан (My University, 2024)
The theoretical foundations of stamping technology play an important role in various fields of industry. They encompass factors such as metal cutting, metal processing, plastic molding, design theory, and mold technology. Understanding these theories provides the opportunity to develop optimal processes and methods used in the production of metal and plastic stamps. By studying these theoretical foundations, one can improve the quality of manufactured products, reduce tool and mold wear, and increase production efficiency. Overall, the theoretical foundations of stamping technology are a key element in the development of new products and technologies in manufacturing processes.
Optimization of production of tool parts for cutting dies
Keywords: Brief Information about Cutting Dies and Punching Machines; Чертеж выбивного станка